Effects of Carboxytherapy on Metabolic Health: A Narrative Review - Arellano-Salazar, Martha P. (2025)
Carboxytherapy is a medical technique that utilizes carbon dioxide for therapeutic purposes. The aim of this review was to assess the scientific evidence on the effects of carboxytherapy on metabolic health. The applications of carboxytherapy span various fields of medicine. Evidence shows that carbon dioxide is not only a key regulator of blood pH but also modulates gene expression, growth factors, and stimulates the production of endothelial progenitor cells. These effects are reflected in increased microcirculation in the skin (where collagen production is stimulated), in subcutaneous adipose tissue (where lipolysis and tissue reduction have been observed), in muscle (where it promotes mitochondrial biogenesis and muscle fiber differentiation), and in bone (where it stimulates repair). The activation of microcirculation is mediated by the upregulation of vascular endothelial growth factor. Despite the existing evidence, further research on the application of carboxytherapy in different medical fields is needed.